Finding an unseen God : reflections of a former atheist - Chole, Alicia Britt (Minneapolis, Minn. : Bethany House, 2009)
"Presents the author's personal journey from atheism to Christianity. Examines the mysteries of life and faith, including how different religious belief systems influence a person. Intended for atheists, agnostics, and theists"--Provided by publisher.
Includes bibliographical references.
Keywords: Chole, Alicia Britt; Christian converts -- United States -- Biography; Atheists -- United States -- Biography; Atheists; Christian converts; United States; Biography